transXpress: a Snakemake pipeline for streamlined de novo transcriptome assembly and annotation - Fallon, Timothy R; Čalounová, Tereza; Mokrejš, Martin; Weng, Jing-Ke; Pluskal, Tomáš (BMC bioinformatics, 2023)
BACKGROUND: RNA-seq followed by de novo transcriptome assembly has been a transformative technique in biological research of non-model organisms, but the computational processing of RNA-seq data entails many different software tools. The complexity of these de novo transcriptomics workflows therefore presents a major barrier for researchers to adopt best-practice methods and up-to-date versions of software. RESULTS: Here we present a streamlined and universal de novo transcriptome assembly and annotation pipeline, transXpress, implemented in Snakemake. transXpress supports two popular assembly programs, Trinity and rnaSPAdes, and allows parallel execution on heterogeneous cluster computing hardware. CONCLUSIONS: transXpress simplifies the use of best-practice methods and up-to-date software for de novo transcriptome assembly, and produces standardized output files that can be mined using SequenceServer to facilitate rapid discovery of new genes and proteins in non-model organisms.
Keywords: Transcriptome; RNA-Seq; software; Gene Expression Profiling; stanovení celkové genové exprese; High-performance computing; RNA-seq; Reproducible software; sekvenování transkriptomu; Software; Non-model organisms; Sequence Analysis, RNA; anotace sekvence; De novo transcriptome assembly; transkriptom; Molecular Sequence Annotation; sekvenční analýza RNA; Differential expression analysis; Transcriptome annotation